THE ROLE OF ISLAMIC BOARDING SCHOOL DARUL KHAIRAT PONTIANAK IN FORMING SANTRI CHARACTERS - Sahrul Layali; Jagad Aditya Dewantara (Widyagogik, 2022)
This study aims to determine how the Role of Darul Khairat Islamic Boarding School Pontianak in Forming the Character of Santri. This research method uses a qualitative approach with descriptive research type. Sources of data in this study are the results of observations on the activities of the Darul Khairat Pontianak Islamic Boarding School, interviews with educators, administrators, and students of the Darul Khairat Islamic Boarding School in Pontianak, as well as documentation in the form of documents from the Darul Khairat Islamic Boarding School Pontianak and photos during the research implementation. Data collection tools in the form of observation guidelines, interview guides and documentation. The results showed that the Darul Khairat Pondok Pesantren Pontianak has a teaching system that emphasizes character building, as well as educators who have a considerable effort in shaping the character of the santri to produce a generation of santri with character and character.